TAFSIR TEMATIK TENTANG SELEKSI INFORMASI - Siregar, Mawardi (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
This article discusses about how a person behaves when receiving information that comes from trusted people or those who are not trusted. Islam, explains to every Muslim to be selective in receiving information. This selectivity needs to be done to avoid undesirable things. Because errors in receiving information can have a fatal effect on social life. Selective means checking and recharging both the news source and the news delivered, so that the information received is accurate in accordance with the actual conditions